[tex]5^{-8}[/tex] * [tex]5^{10}[/tex] - [tex]7^{-3}[/tex] : [tex]7^{-5}[/tex] +( [tex]\frac{3}{4}^2[/tex])^-1 = [tex]5^{2}[/tex] - [tex]7^{2}[/tex] + ([tex]\frac{3}{4}\\[/tex])^-2 = 25 - 49 + [tex]\frac{16}{9}[/tex] = [tex]-\frac{200}{9}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]5^{-8}[/tex] * [tex]5^{10}[/tex] - [tex]7^{-3}[/tex] : [tex]7^{-5}[/tex] +( [tex]\frac{3}{4}^2[/tex])^-1 = [tex]5^{2}[/tex] - [tex]7^{2}[/tex] + ([tex]\frac{3}{4}\\[/tex])^-2 = 25 - 49 + [tex]\frac{16}{9}[/tex] = [tex]-\frac{200}{9}[/tex]